2011
DOI: 10.1002/ca.21118
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of embalming fluids for use in surgical workshops

Abstract: There is a growing need to learn surgical skills without risk to patients. One of the major determining factors on the suitability of specimens for surgical workshops is the fluid used for embalming. This study sought to compare three different arterial embalming preparations to a single fresh cadaver. Eleven cadavers embalmed using Graz (single cadaver), Dodge (four cadavers) and Genelyn (five cadavers) preparations were compared using four criteria; joint flexibility measured with a goniometer, tissue pliabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 17 publications
3
98
1
4
Order By: Relevance
“…Vessels in these plexuses are thought to be primarily responsible for intraoperative bleeding (Pavletic, 1991). Small vessel collapse and/or obstruction following death, the effects of cryopreservation and individual variations (Jaung et al, 2011) may have accounted for differences in tissue perfusion in this study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Vessels in these plexuses are thought to be primarily responsible for intraoperative bleeding (Pavletic, 1991). Small vessel collapse and/or obstruction following death, the effects of cryopreservation and individual variations (Jaung et al, 2011) may have accounted for differences in tissue perfusion in this study.…”
Section: Discussionmentioning
confidence: 89%
“…Several factors may have accounted for undesirable changes documented in intraabdominal organs in 3 out of 23 cadavers studied. Time to preservation and cause of death (Silva et al, 2007), as well as body condition (i.e., muscle mass and obesity) and individual variations may impact the quality of cadavers preserved by identical methods (Jaung et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The use of embalmed cadavers in anatomical research has been shown to cause increased soft tissue stiffness and decreased joint flexibility in comparison to fresh-frozen cadavers. 22 While all specimens in this study were successfully positioned for each measurement, the surrounding musculature had to be removed for proper string placement. This study does not account for individual limitations in range of motion that could be present due to the surrounding musculature.…”
Section: Discussionmentioning
confidence: 99%
“…5 The benefits and pitfalls of other preservation methods have been reported elsewhere. 37 Inexpensive and less biomechanically accurate composite bone models made with either a plastic or foam cortical material are available for use in surgical skills laboratories. 2 Foam cortical shell models are easily sawn, drilled, or broached and are preferred for creating osteotomies or placing arthroplasty components.…”
Section: Composite Bone Models In Surgical Educationmentioning
confidence: 99%